2010
DOI: 10.1007/s12046-010-0012-2
|View full text |Cite
|
Sign up to set email alerts
|

Size effect in self consolidating concrete beams with and without notches

Abstract: The aim of this study is to obtain the fracture characteristics of low and medium compressive strength self consolidating concrete (SCC) for notched and un-notched plain concrete beams by using work of fracture G F and size effect model G f methods and comparing them with those of normal concrete and high performance concrete. The results show that; (i) with an increase in compressive strength, G F increases and G f decreases; (ii) with an increase in depth of beam, the decrease in nominal stress of notched be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Numerical methods such as the finite element and boundary element methods [9] are used to determine the stress intensity factor. These methods are applicable to the description of not only different size specimens but also specimens with varying geometry and strength [10,11].…”
mentioning
confidence: 99%
“…Numerical methods such as the finite element and boundary element methods [9] are used to determine the stress intensity factor. These methods are applicable to the description of not only different size specimens but also specimens with varying geometry and strength [10,11].…”
mentioning
confidence: 99%
“…According to CEB-FIB [39], fracture energy can be related with compressive strength in the form of power function. Moreover, various investigators have suggested a direct relationship between these parameters [40,41]. As shown in Figure 11, fracture energy was directly proportional with compressive strength and the relationship could be expressed via the power equation below, with correlation coefficient ( 2 ) of 0.87: = 0.055…”
Section: Fracture Characteristicsmentioning
confidence: 99%
“…Another observation they made was in 2012, when they studied the fracture parameters by varying the depth of the notch and increasing the area of reinforced bars [34]. Eskandari et al [35] also concluded almost similar results but they also compared the results between beam specimens with and without notches.…”
Section: Discrete and Smeared Crack Modelmentioning
confidence: 99%